Characterization of Wp-type of spaces involving fractional Fourier transform - Upadhyay S.K.; Kumar A. (My University, 2025)
The characterizations of Wp-type of spaces and mapping relations between W- and Wp-type of spaces are discussed by using the fractional Fourier transform. The uniqueness of the Cauchy problems is also investigated by using the same transform. © 2015, Upadhyay and Kumar; licensee Springer.